Can the International Court of Justice Shape Global Climate Action Through Law, Authority, and Accountability? - Novita, Anik; Lestari, Eky; Sanni, Tajudeen; Srisawat, Kanya; Min, Zhang; Arifin, Ridwan (Universitas Negeri Semarang, 2024)
Climate change presents an unprecedented challenge to the international legal order, raising urgent questions about responsibility, compliance, and enforcement. This article examines whether the International Court of Justice (ICJ) can meaningfully shape global climate action through its legal authority and judicial functions. It analyzes the Court’s potential role in clarifying states’ obligations under international law, particularly in relation to environmental protection, human rights, and the principle of due diligence. By assessing both contentious cases and advisory opinions, the article explores how the ICJ may influence state behavior even in the absence of direct enforcement mechanisms. The study situates the ICJ within the broader framework of international climate governance, including treaties such as the United Nations Framework Convention on Climate Change and the Paris Agreement. It evaluates how the Court’s interpretations of customary international law, state responsibility, and transboundary harm could contribute to greater legal accountability for climate-related conduct. Particular attention is given to the growing momentum behind climate litigation and recent initiatives seeking advisory opinions on states’ climate obligations. While acknowledging institutional limitations—such as jurisdictional constraints, state consent, and political resistance—the article argues that the ICJ possesses significant normative power. Its judgments and opinions can shape legal discourse, influence domestic courts, and strengthen the legitimacy of climate obligations under international law. Ultimately, the article contends that the ICJ can play a transformative, though indirect, role in global climate action by reinforcing legal standards, enhancing accountability, and contributing to the development of a coherent international response to climate change.